2008
DOI: 10.1364/oe.16.006461
|View full text |Cite
|
Sign up to set email alerts
|

Time domain simulation of electromagnetic cloaking structures with TLM method

Abstract: Abstract:The increasing interest in invisible cloaks has been prompted in part by the availability of powerful computational resources which permit numerical studies of such a phenomenon. These are usually carried out with commercial software. We report here a full time domain simulation of cloaking structures with the Transmission Line Modeling (TLM) method. We first develop a new condensed TLM node to model metamaterials in two dimensional situations; various results are then presented, with special emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…This approach consists basically in substituting the anisotropic medium of the shell by a concentric layered structure of alternating homogeneous isotropic materials. Furthermore, the permittivity and permeability of the layers are calculated very close to their inner boundary (but not rigorously in the vicinity of the boundary in order to avoid divergence of the EM parameters in the first layer) since this procedure has been shown to give the best results [5]. The cloaking entity is illuminated by a Gaussian pulse, which theoretically contains all the frequencies.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach consists basically in substituting the anisotropic medium of the shell by a concentric layered structure of alternating homogeneous isotropic materials. Furthermore, the permittivity and permeability of the layers are calculated very close to their inner boundary (but not rigorously in the vicinity of the boundary in order to avoid divergence of the EM parameters in the first layer) since this procedure has been shown to give the best results [5]. The cloaking entity is illuminated by a Gaussian pulse, which theoretically contains all the frequencies.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The scattering matrix, as well as Eqs. (3)(4)(5), is absolutely unaltered with respect to the classical node, which renders the technique very comfortable to use. For propagation on the x-y plane, the only non-zero field components for a TE mode are E z , H x , and H y .…”
Section: Metamaterials Modeling With a Series Nodementioning
confidence: 99%
See 2 more Smart Citations
“…However, it is well known that a network of left-handed transmission lines (with the position of L and C interchanged) can support backward electromagnetic waves. A TLM node capable of assuming metamaterials naturally arises from these dual structures [3] and, what is more, it was shown that the only modification compared to the usual version is the value of the impedances of the stubs [4].…”
mentioning
confidence: 99%